Two UMP researchers invented LED lights that could last longer - UMP, PNC (2019)
Two Universiti Malaysia Pahang (UMP) researchers, Hisaji Noda and Muhammad Ikram Mohd Rashid, from Faculty of Electrical & Electronics Engineering (FKEE) had successfully created high efficiency Light Emitting Diode (LED) system called ‘UMP USB LED Stick’.